Surrogate-assisted optimization using multi-objective evolutionary techniques applied to mechanical structural design - Passos, João Carlos Pereira (2019)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Mecânica, Programa de Pós-Graduação em Ciências Mecânicas, 2019.